The formation of a unified database on physical subjects - Kozina, S A; Korobkin, D M; Fomenkov, S A; Vasiliev, S S (Journal of physics. Conference series, 2021)
Currently, when applying for registration of an invention, to assess the chances of patenting an object, to determine the novelty, it is necessary to review existing patents. Because at the moment there is a large amount of information about patent documents dispersed in various sources, the search time for a particular document significantly increases. This also happens with magazine articles. In this regard, this article is aimed at solving the above problem by creating a single database. To create the database, we used archives with patent documents in XML format, downloaded from the official RUPTO and USPTO websites. Physical profile journal sites were used for processing journal articles. The software module presented in this article is intended for specialists working in the field of physical Sciences. Using this program, you can search for English-language and Russian-language journal articles and RUPTO and USPTO patents on physical subjects, and get links to documents. The program module is developed in the Python programming language using the BeautifulSoup library, as well as the MongoDB.